2012
DOI: 10.1037/a0026909
|View full text |Cite
|
Sign up to set email alerts
|

Confronting sadness through art-making: Distraction is more beneficial than venting.

Abstract: We examined two ways in which art-making may function to elevate mood-venting (expressing negative feelings) and distraction (expressing something unrelated to the negative feelings). In Study 1 we induced a negative mood in participants by showing them a sad film clip and then assigned them to one of two conditions. In the venting condition they were asked to draw something related to the film; in the distraction condition they were asked to draw an image unrelated to the film (a house). In Study 2 we induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
89
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 30 publications
10
89
1
6
Order By: Relevance
“…Nevertheless, this work highlights an interesting aspect of the puzzle by observing that listeners often feel displeasure due to painful memories whilst listening to music, but this affect is transformed into positive emotion (nostalgia, relief) afterwards. The identification of this "cathartic" experience has long 145 roots in philosophy (Smuts, 2009), but empirical evidence suggests that venting or cathartic processing is less efficient than distraction as a strategy for elevating mood after induced sadness [38]. Finally, it has been suggested that sad music may be experienced as pleasurable due to it's power to overcome cognitive dissonance often associated with negative emotions.…”
mentioning
confidence: 99%
“…Nevertheless, this work highlights an interesting aspect of the puzzle by observing that listeners often feel displeasure due to painful memories whilst listening to music, but this affect is transformed into positive emotion (nostalgia, relief) afterwards. The identification of this "cathartic" experience has long 145 roots in philosophy (Smuts, 2009), but empirical evidence suggests that venting or cathartic processing is less efficient than distraction as a strategy for elevating mood after induced sadness [38]. Finally, it has been suggested that sad music may be experienced as pleasurable due to it's power to overcome cognitive dissonance often associated with negative emotions.…”
mentioning
confidence: 99%
“…For example, the 'flow state', a state of deep absorption, may improve wellbeing by providing temporary distraction from debilitating experiences or thoughts, or through the self-affirming nature of the experience itself and associated feelings of accomplishment. 16,17,18 Given the breadth of explanations for a link between art-making and health, the current study carefully selected indices of affect, cognition, self-regulation and state of consciousness, in order to evaluate changes in these following art-making in daily life.…”
mentioning
confidence: 99%
“…Para ello se evaluó la relación entre los aspectos cognitivos y las emociones de los participantes al realizar una actividad gráfica encaminada a disminuir el estrés cotidiano. Siguiendo a Huss et al (2012) y Drake & Winner (2012a, 2012b, las actividades artísticas pueden ser usadas como un mediador que permite ya sea expresar o distraerse de los estresores. Nuestros resultados indican que ambos usos dan pie a la disminución tanto de las emociones como del estrés percibido.…”
Section: Discussionunclassified
“…Desde este último se ha trabajado su reducción tras la inducción mediante estímulos adversos como películas (Drake, Coleman & Winner, 2011) e incluso trabajando con los propios estresores (Vanegas-Farfano, Quezada-Berumen & González Ramírez;. Mediante este tipo de investigaciones, se ha logrado aislar y corroborar los distintos elementos que están en juego durante este proceso: se sabe que existen distintas formas para manejar los estresores, los cuales se orientan a la solución del problema que lo origina o el dejar de atenderle (Aydin, 2010;Drake & Winner 2012a); y que esto se encuentra arraigado en las primeras formas de afrontamiento desarrolladas desde la infancia (Drake & Winner, 2012b).…”
Section: Efectos De La Actividad Artística En La Reducción Del Estrésunclassified
See 1 more Smart Citation